Windows to Malaysia : [cakera padat multimedia] the comprehensive and exclusive encyclopedia of Malaysia (Kuala Lumpur : Cosmopoint, 1997)
Covering four main groups: 1. Land and People -- 2. Business -- 3. Politics -- 4. Tourism